2012
DOI: 10.1017/s0031182012001187
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in mononuclear cell subpopulations in dogs immunized with gentamicin-attenuatedLeishmania infantum

Abstract: The impact of immunization with gentamicin-attenuated Leishmania infantum (H-line) on the immunophenotypic profile of popliteal lymph node (PLN) and peripheral blood mononuclear cells (PBMCs) of dogs was assessed by flow cytometry and immunohistochemistry. Compared with the dogs infected with L. infantum wild-type (Group WT), there was a significantly higher percentage of CD4+, CD44+ T cells and CD14+, MHC-II+ cells and a lower percentage of CD4+ CD25+ regulatory T cells in PLN of the immunized dogs with L. in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
(93 reference statements)
1
4
0
Order By: Relevance
“…[6,7,16] However, an association between production of NO and increased apoptosis of PBMC cells and splenic leukocytes was not observed in dogs with VL in this study, suggesting that the process of cell death is triggered by other means as previously described, sFAS, sFASL and caspase-3 are increased in splenic extracts from dogs infected with VL [7], and mFAS and mFASL levels were also increased in CD4 + and CD8 + T cells in the blood and splenic cells of dogs with VL. [16] The frequency of CD14 + cells, a phenotypic marker for canine macrophages [28], was higher in PBMC and spleen leukocytes of infected dogs confirming previous studies. An increase in CD14 + cells was also observed in the peripheral blood of dogs with VL [29].…”
Section: Discussionsupporting
confidence: 84%
“…[6,7,16] However, an association between production of NO and increased apoptosis of PBMC cells and splenic leukocytes was not observed in dogs with VL in this study, suggesting that the process of cell death is triggered by other means as previously described, sFAS, sFASL and caspase-3 are increased in splenic extracts from dogs infected with VL [7], and mFAS and mFASL levels were also increased in CD4 + and CD8 + T cells in the blood and splenic cells of dogs with VL. [16] The frequency of CD14 + cells, a phenotypic marker for canine macrophages [28], was higher in PBMC and spleen leukocytes of infected dogs confirming previous studies. An increase in CD14 + cells was also observed in the peripheral blood of dogs with VL [29].…”
Section: Discussionsupporting
confidence: 84%
“…The progression of leishmaniosis in dogs is associated with humoral response and depression of cellular immunity [27]. We previously reported that L. infantum H-line induced a CD4 + Th1 response which was characterized by the production of relatively higher levels of IFN-γ and lower levels of IL-10 compared with those in the dogs infected with wild-type parasite [18], [19]. In contrast to L. infantum WT, the attenuated parasite was unable to multiply and survive in the visceral organs of immunized dogs [17] and remained localized in the skin at the site where the promastigotes were injected.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the attenuated line failed to spread to, and within, the visceral organs of BALB/c mice and dogs over a 12 week observation period [17] . Immunohistochemical investigation showed no parasites in the popliteal lymph node (PLN) of immunized dogs whereas there were parasites in the PLN of 60% of dogs infected with L. infantum WT [18] . No clinical signs and histopathological abnormalities were found in the dogs immunized with the attenuated line of parasite over 2 years post-immunization [17] , [19] .…”
Section: Introductionmentioning
confidence: 99%
“…Comparing dogs infected with either WT L. infantum or gentamicin-attenuated L. infantum H-line, no pathological abnormalities were observed in the latter group, which induced significantly higher IFN-γ and lower IL-10 levels with the highest levels of IgG2 subclass in their sera (37). Also, proliferation of mononuclear cells is associated with cellular immunity in immunized dogs (38). However, in addition to the difficulty of large-scale production of these physically attenuated vaccines and their delivery to the field in appropriate conditions, the major drawback is their loss of effectiveness for protective immunity due to their inability to form sub-clinical infection and express critical antigen epitopes (30) (Table 2).…”
Section: Live Chemically Attenuated Vaccinesmentioning
confidence: 99%